1999
DOI: 10.2337/diabetes.48.8.1600
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular triglyceride content is a determinant of in vivo insulin resistance in humans: a 1H-13C nuclear magnetic resonance spectroscopy assessment in offspring of type 2 diabetic parents.

Abstract: Insulin resistance is the best prediction factor for the clinical onset of type 2 diabetes. It was suggested that intramuscular triglyceride store may be a primary pathogenic factor for its development. To test this hypothesis, 14 young lean offspring of type 2 diabetic parents, a model of in vivo insulin resistance with increased risk to develop diabetes, and 14 healthy subjects matched for anthropomorphic parameters and life habits were studied with 1) euglycemic-hyperinsulinemic clamp to assess whole body i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
623
6
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(669 citation statements)
references
References 43 publications
36
623
6
4
Order By: Relevance
“…IMTG is best correlated with an individual's degree of insulin resistance, regardless of BMI [6][7][8]. No differences in IMTG were observed in LGI or HGI, indicating that hyperglycaemia-hyperinsulinaemia is not sufficient to elicit higher levels of IMTG in myotubes of post-diabetes mellitus participants.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…IMTG is best correlated with an individual's degree of insulin resistance, regardless of BMI [6][7][8]. No differences in IMTG were observed in LGI or HGI, indicating that hyperglycaemia-hyperinsulinaemia is not sufficient to elicit higher levels of IMTG in myotubes of post-diabetes mellitus participants.…”
Section: Discussionmentioning
confidence: 91%
“…The molecular mechanisms responsible for the progression of insulin resistance are still poorly understood. Ectopic accumulation of lipid in skeletal muscle (intramuscular triacylglycerol [IMTG]) is associated with obesity and highly correlated with the development of insulin resistance [6][7][8]. However, the observation that lean, insulin-sensitive endurance-trained athletes have high levels of IMTG has led to the hypothesis that altered or incomplete lipid metabolism may be an important factor in the progression of insulin resistance (reviewed by van Loon and Goodpaster [9]).…”
Section: Introductionmentioning
confidence: 99%
“…The IMCL content, which in many [1][2][3][4] but not all studies [45,46] has been shown to be increased in insulin resistance, was also one focus of our experiments. The effects of TGRLs on insulin signalling and glucose homeostasis followed a time-dependent fashion.…”
Section: Discussionmentioning
confidence: 96%
“…high plasma levels of NEFAs, dyslipidaemia and pronounced postprandial lipaemia. A fourth lipid abnormality suggested to be a determinant of insulin resistance is the increase of intramyocellular lipid (IMCL) content in skeletal muscle [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the association between elevated plasma NEFA concentrations, intramyocellular triacylglycerol (IMTG, often also abbreviated to IMCL) accumulation and the development of insulin resistance and/or type 2 diabetes [1][2][3][4][5][6][7]. The Randle (glucose-fatty acid) cycle has often been used to explain the mechanism behind skeletal muscle insulin resistance induced by fatty acid (FA) [8].…”
Section: Introductionmentioning
confidence: 99%